Peningkatan Kepercayaan Ibu Postpartum dalam Merawat Bayinya Melalui Bonding Attachment - Ratna Hidayati (Universitas Airlangga, 2007)
Introduction: Bonding attachment is one of the methods to support an excessively interaction between mother and her’s baby. This interaction may facilitate a mother to be more confident to take care of the baby. Method: This study was used a quasy-eksperimental design which is the objective of this study was to examine the influence of facilitated bonding attachment to mother’s confidence to take care of her baby at early postpartum period in Amelia Pare Kediri Hospital. There were 90 respondents who met to the inclusion criteria and taken by using purposive sampling technique, divided into control group and intervention group. Data were collected by using questionnaire, then it were analyzed by using Chi Square and t-Test. Result: The result showed that nurse behaviour had significance effect on facilitated bonding attachment to mother/women self confidence to take care of her baby at early postpartum period (p=0.000). Discussion: It can be concluded that nurses behaviour who facilitated bonding attachment influenced mother’s confidence to take care of her baby at early postpartum periode. Then family center nursing care plan should applied in all of health care setting to promote family empower and to obtain bonding attachment since newborn. Moreover, nursing companion during the care is also important to facilitate mother’s ability to take care of the baby.